ANALISIS KESALAHAN SISWA KELAS IX-G DI SMP NEGERI 3 CIMAHI DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIK PADA MATERI LINGKARAN - Febriananingsih Timutius; Nadya Rahma Apriliani; Martin Bernard (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
The purpose of this research is to describe the student's mistake in solving the problem of mathematical problem solving. The method used in this research is descriptive qualitative. This research was conducted in class IX-G SMP Negeri 3 Cimahi with the number of students as much as 38 people. The data obtained from the written test about the problem solving ability of mathematics as much as 5 questions. Based on the results of research conducted from the test 5 problem solving mathematical problems only 29% of students who master the problem of solving mathematical problems, means 71% of students do not master the problem of problem solving mathematics. The average value of students is 5.68 with highs of 13 and lows one of the maximum value of 20. From the analysis of the responses of the students, there were some mistakes made by the students in solving the problem is: The process of settlement is not systematic, not No settlement process, directly to the answer, many do not wear the unit of length and wide, mistakenly write unit area and length, some even wearing unit volume, do not understand the problem, the conclusions are not relevant to the result of the settlement, mistaken in identifying the image, settlement which is not complete, so it can be concluded that the mathematical problem solving ability of grade IX-G students in SMP Negeri 3 Cimahi is still low.